PENGARUH TRANSPARANSI DAN AKUNTABILITAS TERHADAP KINERJA DAN DAMPAKNYA PADA DAYA SAING PT JASA LAYANAN PEMELIHARAAN - Kristiana Live Sonya; Anna Wulandari (LP2M Sekolah Tinggi Ilmu Ekonomi IPWI Jakarta, 2017)
This study aimed to obtain factual and conceptual information about how much influence Transparency and Accountability Against Corporate Performance And Its Impact on Competitiveness.The population in this study were all employees of PT Jasa Layanan Pemeliharaan as many as 152 people. The technique used is the technique Observations / survey using a questionnaire (questionnaire) of the respondents. Sampling using random sampling, and the number of samples taken is determined as 110 respondents / employees. The model developed in this study consists of three hypotheses were tested using Structural Equation Modeling of the statistical program SPSS and AMOS 21 as a tool of analysis.Research results derived from the survey results and the processing and analysis of data, obtained by multiple linear regression model standardized Y (ɳ1) = 0.387ξ1 + 0.637ξ2 + ErrorVar = 0.000009, R² = 0.9999, which means that the HR Strategy affect the Company's performance with coefficient by g1 = 0.387; P value = 0.001; CR = 3,595 and Financial Strategy affect the Company's performance with a coefficient of g2 = 0637; P value = 0.001; C.R = 5341. While Effect on Corporate Performance Company Competitiveness shown in the standardized linear regression model; Competitiveness (ɳ2) = 0956 + Errorvar ɳ1 = 0.000676; R² = 0.999324 with a regression coefficient of β = 0956; P value = 0.001; CR = 8418 means the better the company's performance will increase the Company's Competitiveness. Keywords:Transparency, Accountability, Performance, Competitiveness